In Situ Characterization Method to Reveal the Surface Reconstruction Process of an Electrocatalyst - Yiqin Zhan; Tao Yang; Shuang Liu; Liming Yang; Enhui Wang; Xiangtao Yu; Hongyang Wang; Kuo-Chih Chou; Xinmei Hou (Nanomaterials)
Renewable energy-driven water electrolysis is widely regarded as a pivotal approach for achieving carbon-free hydrogen production. The development of highly efficient electrocatalysts is crucial to advancing the efficiency and scalability of electrolytic water splitting. Recent advancements in characterization techniques have revealed that catalysts often undergo surface reconstruction during the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), leading to the formation of real active species. Understanding the surface reconstruction process through advanced characterization methods is essential for the rational design of high-performance catalysts. However, the surface reconstruction of catalysts is a highly complex phenomenon, and conventional ex situ characterization techniques often fall short of capturing the dynamic evolution of the catalyst surface. Consequently, in situ characterization methods have emerged as indispensable tools for elucidating the surface reconstruction process. This paper provides a detailed review of the process of surface reconstruction, the reasons behind it, and the in situ characterization methods, and finally discusses the challenges faced by the characterization methods for the reconstruction of water electrolysis catalysts in future development.